Innate iNKT cells: from biological insight to clinical impact - Rotolo, Antonia; Mason, Nicola J.; Exley, Mark A. (Frontiers in Immunology, 2025)
Over the past 30 years, work of immunologists worldwide has phenotypically and functionally defined “Natural Killer T cells” (NKT) and their subsets, including “invariant Natural Killer T cells” (iNKT). NKT cells make up a substantial fraction of T cells that express NK cell markers and have TCRs restricted to either conventional MHC molecules or the monomorphic CD1d molecule. Among these, iNKT cells are CD1d-restricted and more common within NKT cells than T cells without NK markers. While the definition of NKT cells, whether based on phenotype, function, or both, remains a topic of debate, iNKT cells represent a distinct T cell population characterized by a recurrent, conserved TCR rearrangement (TRAV10–TRAJ18 in humans) paired with a limited Vβ repertoire (mostly encoded by TRBV25-1 in humans). iNKT cells are restricted by CD1d, which, unlike CD1a-c molecules, is expressed not only on professional antigen-presenting cells and thymocytes but also on certain non-hematopoietic somatic tissues, both normal and neoplastic. Like all CD1 family members, CD1d presents various lipid antigens by accommodating their long hydrophobic tails in deep binding pockets, in contrast to the shallow peptide grooves of conventional MHC molecules. However, the ligand repertoire of CD1d is distinct from that of CD1a-c. This review focuses on CD1d-restricted iNKT cells. Activation of iNKT cells via their semi-invariant TCR, often in synergy with NK receptors and other co-stimulatory molecules, triggers a rapid, polyfunctional response. Unlike conventional MHC-restricted T cells, individual iNKT cells can simultaneously produce both Th1- and Th2-type cytokines and exert cytotoxic activity in an immune synapse-directed fashion. Through this combination of direct cytotoxicity and cytokine-mediated immunomodulation, iNKTs can eliminate target cells while activating myeloid and other lymphoid populations to amplify immune responses. Their versatility has fueled growing interest in harnessing iNKT cells across inflammatory, infectious, and oncological diseases, where early-phase studies have demonstrated their safety and preliminary efficacy. Moreover, because they are restricted by the non-polymorphic CD1d molecule and possess immune-regulatory properties, iNKT cells lack graft-versus-host potential, making them ideal candidates for allogeneic, off-the-shelf therapies. This review summarizes how iNKT cells are being reimagined as innovative tools for immune intervention across a range of clinical settings.